2022
DOI: 10.1186/s40813-022-00254-1
|View full text |Cite
|
Sign up to set email alerts
|

The mycotoxin deoxynivalenol (DON) can deteriorate vaccination efficacy against porcine reproductive and respiratory syndrome virus (PRRSV) at subtoxic levels

Abstract: Background Feedgrain contamination with mycotoxins, including deoxynivalenol (DON, “vomitoxin”) is relatively frequently encountered. Pigs are particularly sensitive to the toxicity of DON. To assess the interplay between DON and porcine reproductive and respiratory syndrome virus (PRRSV), we performed an experimental DON exposure–PRRSV vaccination–challenge infection trial. Three-week-old piglets were divided into four groups. Groups I, II and III (10 animals/group) were vaccinated with a PRRS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Hence, one common finding of the three studies addressing PRRSV-specific antibodies following vaccination (Sarvard et al 2015 ; Rückner et al 2022 ; this study) is a reduction in antibody S/P ratios at DON concentrations of 2 ppm or higher. The time point of this effect post-vaccination seems to vary (Sarvard et al 2015 and Rückner et al 2022 : day 13/14 onwards, our study: day 28) but may also be influenced by the type of PRRSV vaccine. Sarvard et al ( 2015 ) and Rückner et al ( 2022 ) used a PRRSV-2 MLV, whereas in our study a PRRSV-1 MLV was used.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Hence, one common finding of the three studies addressing PRRSV-specific antibodies following vaccination (Sarvard et al 2015 ; Rückner et al 2022 ; this study) is a reduction in antibody S/P ratios at DON concentrations of 2 ppm or higher. The time point of this effect post-vaccination seems to vary (Sarvard et al 2015 and Rückner et al 2022 : day 13/14 onwards, our study: day 28) but may also be influenced by the type of PRRSV vaccine. Sarvard et al ( 2015 ) and Rückner et al ( 2022 ) used a PRRSV-2 MLV, whereas in our study a PRRSV-1 MLV was used.…”
Section: Discussionmentioning
confidence: 61%
“…The time point of this effect post-vaccination seems to vary (Sarvard et al 2015 and Rückner et al 2022 : day 13/14 onwards, our study: day 28) but may also be influenced by the type of PRRSV vaccine. Sarvard et al ( 2015 ) and Rückner et al ( 2022 ) used a PRRSV-2 MLV, whereas in our study a PRRSV-1 MLV was used. Following challenge infection, in our study and in Rückner et al ( 2022 ) reduced antibody S/P ratios persisted 7–14 days post-challenge infection onwards with DON doses of 2.81 ppm or 2 mg/kg, respectively, in comparison to pigs on DON free diets.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Similarly, when vaccinated mice were exposed to 2.0 mg/L of DON through drinking water, the toxin disrupted their immune response by regulating the secretion of chemokines and cytokines which form part of their defensive mechanism against porcine parvovirus ( 119 ). An experimental study further showed that, in pigs, a 4-week exposure to DON reduced the efficiency of vaccines against the clinical signs of PRRSV ( 120 ). Antibody titers against porcine circovirus in the serum were also shown to decrease by 33–40% at day 28 after including 1.0 and 3.0 mg/kg of DON in diets ( 121 ).…”
Section: The Connection Between Viral Infections In Animals and Mycot...mentioning
confidence: 99%